2018
DOI: 10.1111/jdi.12900
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with the occurrence of nausea and vomiting in type 2 diabetes patients treated with glucagon‐like peptide‐1 receptor agonists

Abstract: The present study showed a significant correlation of PPIs or H2RAs, female sex, and diabetic retinopathy with nausea and vomiting in patients with type 2 diabetes treated with GLP-1 RAs. Hence, the occurrence of nausea and vomiting in patients with these factors warrants attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Treatment-by-subgroup analysis of GI TEAEs yielded significant treatment-by-sex interactions for nausea and diarrhea due to different patterns of incidence across dose groups in males and females. While the higher incidence rates in females were not observed in previous dulaglutide trials, higher rates of nausea in females have been documented in other studies involving GLP-1 RA therapies [19,27,28]. Indeed, for reasons not well understood, gastrointestinal symptoms are consistently reported more frequently in females than in males, with or without diabetes [29].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Treatment-by-subgroup analysis of GI TEAEs yielded significant treatment-by-sex interactions for nausea and diarrhea due to different patterns of incidence across dose groups in males and females. While the higher incidence rates in females were not observed in previous dulaglutide trials, higher rates of nausea in females have been documented in other studies involving GLP-1 RA therapies [19,27,28]. Indeed, for reasons not well understood, gastrointestinal symptoms are consistently reported more frequently in females than in males, with or without diabetes [29].…”
Section: Discussionmentioning
confidence: 70%
“…These events are typically mild and tend to peak soon after treatment initiation before decreasing in the following weeks [15,17]. While the frequency of gastrointestinal (GI) TEAEs can be dose dependent [18,19], previous studies involving GLP-1 RA therapies have shown that escalating the dose in a measured, stepwise manner can lessen the occurrence and severity of GI events [20,21]. The AWARD-11 trial compared the efficacy and safety of dulaglutide at once-weekly doses of 3.0 mg and 4.5 mg with its efficacy and safety at the previously approved 1.5-mg dose [22], with dose escalation occurring every 4 weeks from the 0.75-mg starting dose to mitigate potential tolerability issues at higher doses.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, peripheral administration of LiCl induces cFos neuronal activity in the IPBN, the AP and the NTS [726,729] with remarkable overlap in the cFos activity pattern induced by centrally administered GLP-1 [726]. Apart from inducing cFos activity in the same brain areas [696,726,730], LiCl and central GLP-1R agonism both decrease locomotor activity [668,731], slow GI motility and gastric emptying [573,732], reduce body temperature [732,733], and induce adverse gastrointestinal effects including nausea, emesis, and taste avoidance [696,[724], [725], [726],[734], [735], [736], [737]]. Selective ablation of NTS PPG neurons prevents stress-induced hyperphagia in mice but has no effect on long-term ad libitum food intake, body weight, or glucose tolerance [90].…”
Section: Glp-1 Effects On Food Intake and Body Weightmentioning
confidence: 99%
“…Conversely, the most common side effects associated with treatment for obesity and type 2 diabetes with GLP-1 analogs are nausea and vomiting. These symptoms may be more frequent in women and those also treated with metformin, proton pump inhibitors, and/or anti-histamines [ 165 , 166 ]. While nausea and vomiting associated with weight loss from liraglutide treatment is often transient [ 167 ], occurrence of these side effects still limits the therapeutic potential of GLP-1 analogs.…”
Section: Aversionmentioning
confidence: 99%